ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PT TITIAN KALTIM DI SAMARINDA - mi Kulsum3, Resti Budianti1, Titin Ruliana2 (EKONOMIA, 2020)
The purpose of this study is to find out the financial performance of PT. Titian Kaltim in 2014 to 2016 term of liquidity, solvency and profitability ratios.The theoritical basis used is financial performance. The analytical tool in this study uses liquidity ratios including current ratio, quick ratio solvency ratio including debt to assets ratio, debt to equity ratio and profitability ratios including return on assets, return on equity.The method used is field research, which is observasing in PT. Titian Kaltim Samarinda and library research, which is collecting information from books and journals.The results of this study in terms of liquidity ratios based on the current ratio and quick ratio variables in 2014, 2015 and 2016 have decreased because debt is increasing every year and cannot be covered by company assets and capital. Judging from the solvency ratio based on the variable debt assets ratio and the debt equity ratio in 2014, 2015 and 2016, the results were not good because the companies in managing their assets were financed more by creditors rather than from assets or capital of the company. In terms of profitability ratios based on the variables return on assets and return on equity in 2014, 2015 and 2016, the results were not good because the company's profits each year were less than the maximum and the needs of the company's assets and capital invested